Effect of Poly (N-IsoPropylAcrylamide) “PNIPAM” on Hepatic Cells of Swiss Albino Mice, Mus musculus - Aslam, Md. Imtiyaz; Verma, Rohit Kumar; Roy, Richa; Roy, S. P. (International Journal of Applied Sciences and Biotechnology, 2013)
The present paper deals with the effect of polymeric compound poly (N-isopropyl acrylamide) “PNIPAM” for their toxicity on hepatic cells. The nanoparticle is a xenobiotic compound that accumulates in the liver for their metabolism. Non-metabolizing xenobiotic compounds such as PNIPAM produces anomalies in the hepatic cells. Certain enzymes such as ALT and ALP can be assayed for the hepatocytic toxicity. An attempt has been made to know the toxic effect of “PNIPAM” in a concentration of 0.8mg/ml on the hepatic cells of Swiss Albino mice, Mus musculus. The ALT and ALP analysis were performed through test kits for their quantitative estimation. The histological result shows that several lesions were produced after the introduction of aqueous solution of PNIPAM for an incubation period of 48 hours. The toxicity was confirmed Spectrophotometrically by the assessment of enzyme ALT and ALP. The increased concentration of ALT (55.0 IU/L) and slight decrease in ALP (40.0 IU/L) concentration was responsible for the metabolic alteration and production of hepatocytic anomalies in the mice. DOI: http://dx.doi.org/10.3126/ijasbt.v1i4.9104 Int J Appl Sci Biotechnol, Vol. 1(4): 208-213